Comparisons Between First Person Point-of-View 180° Video Virtual Reality Head-Mounted Display and 3D Video Computer Display in Teaching Undergraduate Neuroscience Students Stereotaxic Surgeries - Neuwirth, Lorenz S.; Ros, Maxime (Frontiers in Virtual Reality, 2021)
The current study compared a head mounted display first-person-point-of-view immersive virtual reality applications (HMD-FPV IVRA) and computer displayed first person point-of-view semi-immersive virtual reality applications (CD-FPV SIVRA) to address learning gaps inadvertently created by textbooks that insufficiently teach about stereotaxic surgery, by bringing students into and through the procedures of the research techniques using a virtual reality educational instruction platform/technology designed by Revinax® Virtual Training Solutions. Students completed the learning modules and were surveyed to determine their ratings of the learning content, how it compared to a traditional lecture, online/hybrid lecture, YouTube/other video content, would they have interest is such a pedagogical tool, and their comprehension of the material they learned. The results showed that students found both HMD-FPV IVRA and CD-FPV SIVRA to have equal benefit in helping them attend to and learn the material, improve their self-study, and would recommend their college/university to invest in this type of pedagogy. The students reported equal value from both interventions to increase their rate of learning, retention of the material, and its translatability. The results showed, that students prefer to learn in and achieve greater learning outcomes from both HMD-FPV IVRA and CD-FPV SIVRA over other pedagogical instructional formats. Students felt that either HMD-FPV IVRA or CD-FPV SIVRA would be a more humane alternative to demonstrate the surgical procedure without having to unnecessarily use/practice on an animal just to teach a concept to facilitate their learning in laboratory class consistent with the 3-Rs in animal research and ethics. Both the HMD-FPV IVRA and CD-FPV SIVRA can be a low-cost and effective pedagogical option for learning content to be displayed to students for applied learning to develop skills such as stereotaxic surgery, which suggests this pedagogical approach can be developed for other neuroscience techniques. These pedagogical options using HMD-FPV IVRA and CD-FPV SIVRA to teach students in the neurosciences and associated medical allied fields can be of significant educational value, especially in the current COVID-19 climate where distance learning has posed a range of limitations to learning since face-to-face in-person learning has been put on pause until it can resume safely.